The Influence of Product Quality, Price, and Service Qualtity Towards Customer’s Purchase Decisions - Cahyadi, Andre Dhika; Arif , Moh. Erfan (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2023)
This study aims to determine the influence of product quality, price, and service quality variables on purchase decisions in Kopi Studio 24 Malang. This is a kind of explanatory research that explained the correlation and influence between one variable and another by submitting a hypothesis through the submission of hypothesis. This study employed sample of 115 respondents who have ever purchase Kopi Studio 24 product’s by distributing online questionnaires and also used Non-Probability Sampling and Purposive Sampling techniques. This questionnaire method used to find out more about what are the factors behind consumer interest, that make them purchase Kopi Studio 24 products. Then, the data analysis used multiple linear regression and hypothesis test (t-Test) to obtain the independent variable (product quality, price, and service quality) that have influence on dependent variable (purchase decisions) by using the SPSS version 25 program. In addition, the research findings of product quality, price, and service quality have a positive and significant influence the purchase decision. It is expected that the results of this research can become a reference standard for Kopi Studio 24 for improving business performance in the future. Abstrak Penelitian ini bertujuan untuk mengetahui pengaruh dari variabel kualitas produk, harga dan kualitas layanan terhadap keputusan pembelian di Kopi Studio 24 di kota Malang. Jenis penelitian ini adalah explanatory research yang menjelaskan hubungan dan pengaruh antar variabel dengan pengajuan hipotesis. Penelitian ini menggunakan sampel dari 115 responden yang pernah membeli produk Kopi Studio 24 dengan menyebarkan kuesioner online. Teknik pengambilan sampel menggunakan non-probability sampling dan metode purposive sampling. Metode kuesioner digunakan untuk mengetahui apa saja faktor yang menarik minat konsumen untuk membeli produk Kopi Studio 24. Analisis data dalam penelitian ini menggunakan Analisis Regresi Linear Berganda dan uji hipotesis (t-Test) untuk mengetahui variabel bebas (kualitas produk, harga, dan kualitas layanan) memiliki pengaruh terhadap variabel terikat (keputusan pembelian) yang diolah dengan aplikasi SPSS v.25. Hasil penelitian menyimpulkan bahwa kualitas produk, harga, dan kualitas layanan berpengaruh positif dan signifikan terhadap keputusan pembelian. Diharapkan hasil penelitian ini dapat menjadi standar acuan untuk Kopi Studio 24 dalam meningkatkan kinerja bisnis ke depannya.